Antibiotic Prescriptions Pattern in Paediatric In-Patient Department Gauhati Medical College and Hospital, Guwahati - Choudhury DK and Bezbaruah BK (Journal of Applied Pharmaceutical Science, 2013)
The objective of the study was to determine the antibiotic prescriptions pattern and to analyze the rationale use of antibiotic in Paediatric in-patient department of Gauhati Medical College & Hospital, Guwahati (GMCH), Assam. An observational and prospective study was carried out for 1 month duration between April to May 2011. The details of the patients were being recorded in a specific format and results were analyzed by descriptive statistic and expressed as mean ±SD. Out of 200 patients, 132 prescriptions received antibiotics, where 77 were male child and 55 were female child. The mean age of the patients was 4.13 ± 3.75 years. The number of antibiotics per prescription was 1.41 ± 0.67. The duration of antibiotic therapy was 6.05 ± 3.45 days and length of hospitalization was 8.91±5.35. In our study, 71% of paediatric patients were on single antibiotic and most of the paediatric patients were receiving parental preparation. Maximum Antibiotic prescriptions were found in the age group of 5-12 years. Cephalosporins (41.5%) were the most commonly prescribed antibiotic group. The most commonly found antibiotics combination in our study were Amoxycillin and Clavulanic acid & Cefotaxime and Sulbactum. The antibiotic prescription should be done in accordance with WHO guidelines and rational strategies should be implemented in order to control antibiotic use mainly focus on patient population especially in children and infants.
Keywords: Paediatric, antibiotic, in-patient.